Trigliserida dan Kolesterol Total sebagai Prediktor Mortalitas Pasien Stroke: Literatur Review: Trygliceride and Total Cholesterol level as the Predictor of Mortality in Stroke Patient: Literature Review - Bagus Rahmat Santoso; Raihana Raihana; Eirene E.M. Gaghauna (LPPM STIKES Guna Bangsa Yogyakarta, 2023)
Stroke is the leading cause of morbidity and mortality worldwide, who rank in 3rd after heart disease and cancer. Data based on the results of Riskesdas 2018 the prevalence of stroke is 10.9% and 15.4% of stroke case caused Indonesia. The province with the 3rd highest incidence is South Kalimantan at 12.7% per mil. Hypertriglyceridemia and hypercholesterolemia are risk factors for ischemic stroke. Low triglyceride and total cholesterol levels contribute to intracerebral haemorrhage. This study to analyse the relationship of laboratory results triglycerides and total cholesterol to mortality in stroke patients. Method: Study are used literature review, searching online journals and sources from databases. Using keywords, namely stroke mortality, total cholesterol, and triglycerides. Results of the literature review, it was found that there were 18 journals were analysed that triglycerides and total cholesterol predictors of prognosis and mortality in stroke patients. Range of values affect is high triglyceride levels > 200 mg/dL and high total cholesterol levels >160-240 mg/dL affect the formation of atherosclerosis effect on blood vessel blockage occurs in ischemic stroke patients. Low triglyceride levels <150 mg/dL and low cholesterol <120-180 mg/dL causes malnutrition which can worse in stroke patients. Low levels of triglycerides and cholesterol effect on the integrity of cell membranes and resistance to rupture, resulting in prolonged bleeding. From this analysis it can be concluded that high or low levels of triglycerides and total cholesterol had effect on prognosis and mortality in stroke patients based on the pathophysiology that occurs.